Dream recall frequency and nightmare frequency in patients with restless legs syndrome (RLS) or periodic limb movements disorder (PLMD) - Schredl, Michael (International journal of dream research, 2022)
Dreaming in patients with sleep disorders, e.g., narcolepsy, insomnia, differs from dreaming in healthy controls. Dream research in patients with RLS/PLMD, however, is very scarce. Overall, 447 patients (263 women, 184 men) with RLS/PLMD and 208 healthy controls completed dream, sleep, and stress questionnaires during diagnostic procedures. The patient group did not show any differences regarding dream recall frequency but reported nightmares more often than healthy controls. This difference was no longer significant after controlling for daytime distress. This study indicates that patients with RLS or PLMD experience more nightmare than healthy persons - most likely due to the daytime burden associated with having this types of sleep disorders. Future research should study whether altered sleep physiology, e.g., vegetative and/or cognitive arousals, has a direct effect on the dreaming process.
Gesehen am 19.10.2022